2009
DOI: 10.1371/journal.pone.0005523
|View full text |Cite
|
Sign up to set email alerts
|

Nest Making and Oxytocin Comparably Promote Wound Healing in Isolation Reared Rats

Abstract: BackgroundEnvironmental enrichment (EE) fosters attachment behavior through its effect on brain oxytocin levels in the hippocampus and other brain regions, which in turn modulate the hypothalamic-pituitary axis (HPA). Social isolation and other stressors negatively impact physical healing through their effect on the HPA. Therefore, we reasoned that: 1) provision of a rat EE (nest building with Nestlets®) would improve wound healing in rats undergoing stress due to isolation rearing and 2) that oxytocin would h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 44 publications
3
46
1
1
Order By: Relevance
“…Herein, it could be demonstrated that OXY is able to ameliorate skin regeneration as given by a fast epithelial recovery with mostly intact dermal structures [13,51]. One major reason for these findings might also be the fact of better social interactions, as group housed rats as well as rats that have been given environmental enrichment presented with overall better healing performances most likely associated with increased OXY and decreased cortisol levels [12,13,51]. On the contrary, it could further be demonstrated that the application of OXY resulted in less remote-to-injury organ damage [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Herein, it could be demonstrated that OXY is able to ameliorate skin regeneration as given by a fast epithelial recovery with mostly intact dermal structures [13,51]. One major reason for these findings might also be the fact of better social interactions, as group housed rats as well as rats that have been given environmental enrichment presented with overall better healing performances most likely associated with increased OXY and decreased cortisol levels [12,13,51]. On the contrary, it could further be demonstrated that the application of OXY resulted in less remote-to-injury organ damage [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Male homozygous SKH-1-h hairless mice (12)(13)(14)(15)(16) weeks old) with a body weight (bw) of 30-40 g were used in the study. The animals were housed in standard laboratories with a 12 h light-dark cycle and had free ad libitum access to standard laboratory food and water.…”
Section: Animals and Woundingmentioning
confidence: 99%
See 2 more Smart Citations
“…Πρόσφατη μελέτη των Vitalo et al (2009) απέδειξε την άμεση θετική επίδρα ση που έχει η προσθήκη υλικού για την κατασκευή φω λιάς στο χρόνο επούλωσης των τραυμάτων σε επίμυες.…”
Section: ο φυσικός εμπλουτισμόςunclassified